Implementation of agroforestry systems in agro-Ecological Model socioproductive medicinal plants held by farmers of the Massif of Pedra Branca, Rio de Janeiro/RJ - Marins, S. R.; Magalhães Fraga, P.A.S.; Ramos, C.M. (Guará Journal, 2025)
The aim of this study is to report the deployment of agroforestry systems in model socioproductive agroecological medicinal plants what happened in the period september to november in the year 2012, with farmers from the Pedra Branca massif municipality of Rio de Janeiro, located in the neighborhoods Vargem Grande and Rio da Prata. The technical team of project Profito Farmanguinhos/FIOCRUZ conducted technical visits on some properties of farmers aiming choose two areas that met the technical conditions. After joint efforts in selected areas, has as a result of the SAF’s deployment in two locations containing fourteen medicinal species.